Optimization of microwave-assisted roasting: Box-behnken design for oxidation of sulfide minerals and control of atmospheric sulfur in refractory gold ore pretreatment - Abdul Hapid; Siti Zullaikah; Mahfud Mahfud; Adji Kawigraha; Mifta Ulul Azmi; Irwan Haryanto; Haswi Purwandanu Soewoto; Alchris Woo Go; Suttichai Assabumrungrat (Case Studies in Chemical and Environmental Engineering)
Response Surface Methodology and Box-Behnken Design have been applied to optimize microwave-assisted roasting of refractory gold ore. The roasting is used as a pretreatment for refractory gold ore to increase gold recovery during leaching. The roasting step consumes high energy and produces high sulfur emissions into the atmosphere. Optimization aims to obtain optimum roasting conditions with minimum energy consumption and sulfur emissions. The effects of microwave power (100–400W), NaClO3 composition (120–360 kg/tonne), water quantity (0–120 kg/tonne), and duration of roasting (5–30 minutes) have been investigated at the preliminary stage. In the optimization stage, three variables were studied with the roasting time fixed at 5 minutes. The optimum conditions for microwave-assisted roasting of refractory gold ore were achieved at 200W, NaClO3 of 200 kg/tonne ore, and water of 150 kg/tonne ore. Based on the optimization model, the predicted temperature and sulfur oxidation are 394 °C and 67.16 %, respectively. Model validation showed that the actual roasting temperature and sulfur oxidation are 404 °C and 67.28 %, respectively. The differences between the predicted and actual values of temperature and sulfur oxidation are 2.5 % and 0.18 %, respectively. With an accuracy surpassing 95 %, the optimization model is capable of predicting both temperature and sulfur oxidation.